Pengaruh Perubahan Suhu pada Modulus Elastik Lapisan Beraspal Perkerasan Lentur dalam Pengujian Regangan yang Berbeda - Hardwiyono, Sentot (Semesta Teknika, 2011)
Flexible pavement strength (Flexible Pavement) is affected by changes in the nature around the changes in temperature affect the strength asphalt layer and seasonal changes (precipitation) affect the strength of the soil layer is not particularly asphalt base. Research to determine the effect of temperature for a layer of flexible pavement in the field can be done in two ways. The first destructive test (Destructive Test, DT) such as core-drill are routed by means of a laboratory test using Universal Testing Machine (UTM). The second test is not destructive (Non Destructive Test, NDT) such as direct field test using a Falling Weight Deflectometer (FWD) and tools Spectral Analysis of Surface Wave (SASW). Testing the temperature of use as has been mentioned with a different strain performed at the Soekarno-Hatta road and highway Cikampek-Purwakarta, Bandung, West Java, Indonesia. Testing methods and testing different strain rates produce different elastic modulus values in testing asphalt flexible pavement layer. The general conclusion, the higher the temperature imposed on the asphalt pavement layer elastic modulus flexural yield whose value has declined. Conversely the lower the temperature imposed on the asphalt pavement layer elastic flexural modulus values produce increasingly rising. Different strain rate testing (FWD, UTM and SASW) on asphalt pavement layer is influenced also by changes in temperature.